The liver in HIV in Africa - Feld, Jordan J; Ocama, Ponsiano; Ronald, Allan (International Medical Press, 2005)
As access to antiretroviral therapy improves across the African continent, liver disease is emerging as an important cause of morbidity and mortality among HIV-infected individuals. Although coinfection with hepatitis B virus (HBV) and hepatitis C virus (HCV), along with highly active antiretroviral therapy (HAART)induced hepatotoxicity appear to be the major causes of liver disease in this population, other diseases endemic to Africa with hepatic manifestations are influenced by HIV infection as well. In this review we present the available data on liver disease in HIV-infected populations in Africa and discuss relevant data from the rest of the world. In addition, we highlight important areas for further study
Keywords: HIV; Liver; Africa